PERLINDUNGAN HUKUM TERHADAP NASABAH DALAM KETENTUAN KONTRAK STANDAR PADA PEMBIAYAAN SYARIAH BANK SYARIAH MANDIRI DIKAITKAN DENGAN KETENTUAN PASAL 18 UNDANG-UNDANG PERLINDUNGAN KONSUMEN (STUDI PADA BANK SYARIAH MANDIRI KRAKATAU MEDAN) - Rommy Yudistira Lubis; Bismar Nasution; Tan Kamello; Utary Maharany Barus (USU LAW JOURNAL, 2014)
AbstractContract used in the implementation of the financing facility of Bank Syariah Mandiri Krakatau Medan to prospective investors. Bank customers who apply for credit financing only have two choices whether to accept the agreement the financing that is standard, or reject the consequences of prospective customers will not get the funds they need. This applies across Bank Syariah Mandiri, both at head office and at branch offices.This research is essential to answer: 1) What is the background of Bank Syariah Mandiri using standard contracts in Islamic financing agreement? 2) How does the implementation of Islamic financing agreement using a standard contract on financing at Bank Syariah Mandiri Krakatau Medan? and 3) What legal protection to customers in the use of standard contract provisions of Islamic finance at Bank Syariah Mandiri Krakatau Medan associated with the provision of Article 18 of Law No.8 of 1999 on Consumer Protection? The results showed that: The interests of customers applying for Islamic finance should be noted and considered a business associate; Uses standard contract with Bank Syariah Mandiri Krakatau Medan should use the principles derived from the Quran and Al-Hadith besides also refer to Civil Code, and Bank Indonesia, the central bank should make arrangements about the use of standard contracts in Islamic finance where these rules.Keywords : Contract Standards; Legal Protection for Customer; Islamic Financing and Credit Agreement.